1984
DOI: 10.1172/jci111646
|View full text |Cite
|
Sign up to set email alerts
|

Selective peripheral dopamine-1 receptor stimulation with fenoldopam in human essential hypertension.

Abstract: Abstract. SKF 82526-J, or fenoldopam, a benzazepine derivative, is a selective dopamine-1 (DA-1) agonist devoid of activity at dopamine-2, alpha-or beta-adrenergic receptors. We studied SKF 82526-J in 10 patients with essential hypertension and five normal control subjects on constant 150-meq sodium, 60 meq potassium intake. In the hypertensive patients, during a 6-d placebo period supine blood pressure and heart rate were stable at 156±6/105±4 mmHg and 76±5 beats/ min, respectively. In response to a single or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 24 publications
4
23
0
Order By: Relevance
“…These DOPA-induced renal (natriuresis) and cardiovascular (BP) responses were enhanced in s-EH patients despite comparable plasma and urinary free dopamine values in both these patients and control subjects. This is in accordance with previous reports of an augmented natriuretic reaction of EH patients to intravenously administered dopamine, 6 dopamine-1 agonist, 7 or a dopamine prodrug 8 attributed to an upregulation of dopaminergjc receptors. Paradoxically, plasma renin activity was depressed despite more natriuresis and lowered BP in s-EH patients but not in control subjects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These DOPA-induced renal (natriuresis) and cardiovascular (BP) responses were enhanced in s-EH patients despite comparable plasma and urinary free dopamine values in both these patients and control subjects. This is in accordance with previous reports of an augmented natriuretic reaction of EH patients to intravenously administered dopamine, 6 dopamine-1 agonist, 7 or a dopamine prodrug 8 attributed to an upregulation of dopaminergjc receptors. Paradoxically, plasma renin activity was depressed despite more natriuresis and lowered BP in s-EH patients but not in control subjects.…”
Section: Discussionsupporting
confidence: 93%
“…7 The finding that the creatinine clearance of s-EH patients at the height of DOPAinduced dopamine generation was lower than that of control subjects, whereas the fractional Na + excretion of s-EH patients was higher (with baseline values of both being comparable), is compatible with an impaired renal hemodynamic but an even upregulated natriuretic (tubular) response to dopamine generated from DOPA. This resembles a similar observation made in response to exogenous dopamine in patients with renal diseases and moderate impairment of renal function.…”
Section: Discussionmentioning
confidence: 95%
“…The time course of the blood pressure reduction we observed agreed well with previous observations in normal subjects (Harvey et al, 1985) and hypertensive patients (Ventura et al, 1984;Carey et al, 1984;Harvey et al, 1986). The postural fall of blood pressure was also documented during passive tilting, when there was an accompanying reflex Time (min) Figure 4 Comparison of blood pressure and heart rate changes produced by isometric hand grip before and after 6 weeks of treatment with fenoldopam 100 mg twice daily.…”
Section: Discussionsupporting
confidence: 89%
“…Increments in HR previously have been observed with orally administered fenoldopam in hypertensive patients. 23 ' 24 Furthermore, in a recent study, we observed that intravenous infusions of fenoldopam in hypertensive patients consistently increased plasma NE levels. 23 Although piribedil is used primarily as a centrally acting DA agonist for the treatment of Parkinson's disease, 26 it also inhibits adrenergic transmission by action on DA 2 receptors.…”
Section: Discussionmentioning
confidence: 78%